2017
DOI: 10.2214/ajr.17.17812
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Approach for ROI-Based Measurements of Proton Density Fat Fraction and R2* in the Liver

Abstract: OBJECTIVE The purpose of this study was to evaluate the reproducibility (interreviewer agreement) and repeatability (intrareviewer agreement) of ROI sampling strategies to measure chemical shift–encoded (CSE) MRI-based liver proton density fat fraction (PDFF) and R2* (1 / T2*). A secondary purpose was to standardize ROI-based liver PDFF and R2* measurements by providing a compromise between measurement reproducibility and repeatability and time burden for image analysts. MATERIALS AND METHODS CSE data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…The largest elliptical ROI that would fit in each of the segments (with minimum area of 2 cm 2 ) was chosen while avoiding large vessels and bile ducts. This strategy has been demonstrated to reduce both intra‐ and interreader variability . The average of the nine liver ROI measurements was averaged together to provide a single MRI‐PDFF estimate for each CSE‐MRI acquisition.…”
Section: Methodssupporting
confidence: 80%
“…The largest elliptical ROI that would fit in each of the segments (with minimum area of 2 cm 2 ) was chosen while avoiding large vessels and bile ducts. This strategy has been demonstrated to reduce both intra‐ and interreader variability . The average of the nine liver ROI measurements was averaged together to provide a single MRI‐PDFF estimate for each CSE‐MRI acquisition.…”
Section: Methodssupporting
confidence: 80%
“…Vu et al demonstrated that sampling strategies that sampled the right lobe exclusively estimated significantly different PDFF values compared to sampling strategies that sampled both lobes of the liver . Campo et al suggested that placing four ROIs (one in each of the anterior, posterior, medial, and lateral segments of the liver) may be a reasonable compromise between minimizing time burden and maximizing reader agreement . Our study adds to those studies by demonstrating that a simple sampling strategy of placing two ROIs in each lobe provides high accuracy for whole liver PDFF estimation using the nine‐ROI average as the reference standard.…”
Section: Discussionmentioning
confidence: 65%
“…Prior studies demonstrated that sampling strategies that included more segments, used larger ROIs, or sampled both lobes of the liver had significantly improved correlation with liver mean PDFF, and that the repeatability of liver PDFF measurements improves as the size and number of ROIs increase . Vu et al demonstrated that sampling strategies that sampled the right lobe exclusively estimated significantly different PDFF values compared to sampling strategies that sampled both lobes of the liver .…”
Section: Discussionmentioning
confidence: 99%
“…For phantoms, a single circular region of interest (ROI) (2 cm diameter) was positioned in a central slice of the phantom, sufficiently large to cover the majority of the cross‐section of each vial, while avoiding the edges and potential volume averaging artifacts. For the human study, we used a previously validated method, with ROIs placed by a trained analyst (Reader 1, B.D.P., abdominal imaging clinical fellow with 5 years of MRI interpretation experience) in each of the nine Couinaud segments of the liver in order to sample representative portions of the entire liver. The PDFF in each of the nine ROIs was averaged as a single composite hepatic PDFF value for every patient and acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…As obesity rates in the United States rise, nonalcoholic fatty liver disease (NAFLD) is becoming increasingly prevalent in both adult and pediatric populations. At the cellular level, NAFLD results from intracellular deposition of triglycerides within hepatocytes, ie, hepatic steatosis.…”
mentioning
confidence: 99%